Competitiveness of Arabian gulf ports from shipping lines' perspectives: Case of Sohar port in Oman - Adil Khalid; Mohamed Al-Mamery (Journal of Industrial Engineering and Management (JIEM), 2019)
Purpose: The purpose of this article is to investigate the factors that encourage shipping lines to use port of Sohar, in Oman. Some selected factors were used to assess to what extent it affects the port choice from shipping lines companies' perspective. These factors include infrastructure, hinterland, connectivity and port's dues. Design/methodology/approach: for this study both quantitative and qualitative methodologies were used. Self-administered questionnaire used for collecting quantitative data while interviews were used to collect qualitative data. Secondary data was collected by reviewing academic literature and recent relevant articles and reports. Findings: Port of Sohar has a better opportunity to be the gateway of the Gulf Cooperation Council (GCC) States and all Cargo could have dropped in the port and transferred to other GCC States by road, rail and other transportation modes. This opportunity is gained by the strategic location of Sohar Port outside of the Strait of Hormuz. It can be concluded that port competitiveness can be improved through strategic location, improved hinterland conditions, port facilities, services cost, volume of cargo, connectivity to other ports and dwell time factor. Research limitations: The research was limited mainly by conducting it only at the port of Sohar because surrounding ports are too far away and it should involve more ports to gain comparative results. Limited number of stakeholders as Port Authority, Oman International Container Terminal (OICT) and shipping lines companies and agents is another limitation. Practical implications: The port can improve its competitive advantages and focus on the investigated factors. The government can also continue in working in the three big infrastructural projects; the new express roads, Sohar Airport and rail network connections with other GCC networks. Originality/value: the study used specific factors that expected to contribute to the shipping lines companies' selection of ports in the gulf region. This could help the port to identify their competitive advantage and how they can use these competencies to improve their competitiveness in relation to other ports in the region.
Keywords: 650; Sohar Port; infrastructure; Hinterland; connectivity; dues; competitiveness